An evaluation of the fixed-dose combination sacubitril/valsartan for the treatment of arterial hypertension. (2nd July 2020) - Wehland, Markus; Simonsen, Ulf; Buus, Niels Henrik; Krüger, Marcus; Grimm, Daniela
ABSTRACT: Introduction: Essential hypertension is a significant risk factor for cardiovascular disease, renal disease, and mortality with increasing prevalence. Despite the availability of various antihypertensive agents, hypertension is still poorly controlled. Therefore, new chemical compounds with antihypertensive efficacy need to be developed. The dual angiotensin II receptor-neprilysin inhibitor LCZ696 is a single molecule synthesized by co-crystallization of valsartan and the neprilysin inhibitor prodrug sacubitril (1:1 molar ratio). Areas covered: This review includes an overview of hypertension and the current pharmacotherapy. The authors summarize the LCZ696 drug chemistry, pharmacodynamics, pharmacokinetics, metabolism, randomized control trials (RCTs), and safety concerns. Databases searched included PubMed, Google Scholar, Embase, and ClinicalTrials.gov. Expert opinion: LCZ696 is effective in hypertension treatment. Short-term RCTs have shown that the highest doses of LCZ696 (200 and 400 mg [q.d.]) were more effective at lowering office and ambulatory blood pressure than angiotensin II receptor blockers (ARB) alone while having a similar tolerability profile. The effects of LCZ696 on hypertensive organ damage are only sparsely investigated and so far no studies have established the impact of LCZ696 on cardiovascular event rates. Future studies should focus on the comparison of LCZ696 and combination therapies already in use such as ARB and calcium channel blockers.